Lietuvos bioetikos komiteto kreipimasis dėl atsakingo pacientų ir visuomenės informavimo apie vakcinaciją nuo COVID-19 - Lithuanian Bioethics Committee (Slauga. Mokslas ir praktika, 2021)
In response to the public debate on COVID 19 vaccination, the Lithuanian Bioethics Committee has issued a Statement urging to draw special attention of health care providers to the importance of the responsible communication about the COVID 19 vaccination with patients and public. This statement is based on the analysis of international organisations’ positions, along with the national legal and ethical regulations. The Committee urges health care providers to promote only reliable and evidence based infor mation on COVID 19 vaccination, and to avoid statements which can cause unnecessary doubts and uncertainty in the public. The Committee also encourages health care provid ers to actively remind patients about the importance of reporting COVID 19 vaccine sid e effects and adverse events.